Desain Lanskap Ekoriparian Babakan Pasar, Bogor - Daisy Radnawati; Desy Fatmala Makhmud (Jurnal Lanskap Indonesia, 2020)
Environmental management, especially the water resources sector in Indonesia is experiencing greater pressure from the use of environmental resources compared to efforts to improve environmental quality. The Ministry of Environment and Forestry (KLHK) has collaborated with society through communities to combine the concept of riparian planning with efforts reducing the pollution load from domestic waste and making the place a center for education and environmental conservation, this concept is called ecoriparian. One of the locations planned for ecoriparian planning is located in the Ciliwung Watershed, located in Babakan Pasar Village, Central Bogor District, Bogor City, West Java. This area is located in a densely populated settlement with a strategic location and is thick with pluralistic values. The approach used in this research refers to Gold's (1980) design process, this stage starts from preparation, inventory, analysis, synthesis, concept and design. The results of this research are expressed in the form of a concept and visual design of the Babakan Pasar Ecoriparian Park which develops potentials on the site, the landscape design uses the Chinese and Sundanese cultural approach as outlined in the spatial concept of elemental form and color selection. In this research, is expected the exsistence of this ecoriparian park can improve the quality of the Ciliwung River, change the mindset of the community regarding river preservation and add to the aesthetic value of an area.